Mal Sebagai Ruang Ketiga: Eksplorasi Perilaku Window Shopping Masyarakat Urban Kota - Mudjiyanto , Bambang; Yanuar, Fit; Launa, Launa (Jurnal Ilmu Komunikasi AKRAB, 2025)
Today, malls have transformed from mere shopping centers (transactions) into strategic social spaces. In dense urban spaces, malls often function as a ‘third space’—a neutral public space outside the home (first space) and workplace (second space)—that facilitates social interaction as well as relaxation and recreational activities. This study will explore window shopping behavior among urbanites as a form of non-transactional participation in the consumerist space. Through a qualitative study using virtual phenomenology and a non-participatory observation approach with mall visitors, this study found that window shopping is not only related to shopping interests but also becomes a social practice that reflects the need for escapism, identity flexing, and the fulfillment of psychosocial needs. Malls provide a comfortable, safe, and well-conditioned environment, making them a primary choice for urbanites to unwind and build social connectivity. These findings indicate that the function of malls has transcended issues of consumerism and commercialization. As a third space, malls have become an important arena for modern urban social life.